Evaluating User Experience of SITASI System using HEART Metrics and Importance-Performance Analysis (IPA) - Harmaniola, Elsa; Ahsyar, Tengku Khairil; Syaifullah, Syaifullah; Anofrizen, Anofrizen; Marsal, Arif (Jurnal Pendidikan Informatika (EDUMATIC), 2025)
SITASI is a web-based system developed to help students manage references and citations for their final projects. Despite its importance, no comprehensive evaluation of the system’s user experience (UX) had been conducted. This study aims to evaluate the UX of SITASI used by students of the Information Systems Study Programme at UIN Suska Riau. Using a quantitative survey method, data were collected from 72 active students from the 2018-2021 cohorts through an online questionnaire. The evaluation was based on the five HEART Metrics dimensions: Happiness, Engagement, Adoption, Retention, and Task Success. Respondents were selected through random sampling using the Slovin formula. Data were analysed using SPSS version 30 for validity, reliability, and Importance-Performance Analysis (IPA). The HEART results indicated high usability levels across all dimensions, with Happiness and Retention scoring highest (73%) and Engagement lowest (70%). IPA showed an average suitability of 92%, with four indicators placed in Quadrant I, signifying urgent areas for improvement. These results serve as a foundation for actionable recommendations to enhance system satisfaction, improve performance, and develop a more user-centered and adaptive SITASI platform.